Review of Manning and Chezy Constant for Some Tertiary Irrigation Canals in The Sei Beras Sekata Village Sei Krio Sunggal Deli Serdang District - Sartono Hasugian; Sumono Sumono; Saipul Bahri Daulay (Universitas Sumatera Utara, 2014)
Roughness of canal give effect to the speed of the water flow in it, which in the next, will affect to the efficiency and size of canal. Factors that affect to the canal roughness values ​​are wet surface canal constituent materials; The physical properties of the soil in canal; Irregularity of the canal; Vegetation growing in canal and scouring and deposition factor in canal. Research results indicated that scouring occured in canal which effect to the irregularities in the canal, so that solidify soil and material loading in canal surface were needed. At the tertiary canal one manning roughness value was 0.0462 and chezy was 13.78; at the tertiary canal two manning roughness value was 0.0387 and chezy was 15.98 and at the tertiary canal three manning roughness values was 0.0574 and chezy was 11.38. Keywords: manning and chezy constant, average flow rate, size of the canal